LE SUÉDOIS COMME LANGUE ÉTRANGÈRE. DE DIFFÉRENTES TECHNIQUES POUR L’ÉVALUATION ORALE ET ÉCRITE DE LA GRAMMAIRE - Roxana-Ema DREVE (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
Swedish as an optional course. Different techniques to evaluate grammar, orally and in writing. The general purpose of this article is to analyze different aspects related to the evaluation of Swedish language skills in the case of students enrolled in an optional course, intermediate level. In order to understand the students' perspective on grammatical exercises, we designed and provided them with a feedback questionnaire regarding both written and oral evaluation.